PENGARUH PENAMBAHAN TERSIER BUTIL HIDROKSI QUINON PADA MINYAK KELAPA OLAHAN PETANI - Amir M, Muh. (Sainstek, 2007)
A study has been conducted on the use of TBHQto prevent rancidity of coconut oil produced by farmers using tradisionalmethods. This study was designed to determine degree ofrancidity of coconut oil with and without additional antioxidants during the storage for 1 and 2 months. The results of this study were: there was no significant diffreance (P0,05) in the degree of coconut oil rancidity at the beginning of the experimenteither with or without additional antioxidant. There was of significant differeance (P